The 15-year national trends of urinary cancers incidence among Iranian men and women; 2005-2020 - Amir-Hossein Mousavian; Gita Shafiee; Ali Sheidaei; Narges Zargar Balajam; Mehdi Ebrahimi; Fatemeh Khatami; Kimiya Gohari; Alisam Aryan; Ali Ghanbari-Motlagh; Afshin Ostovar; Seyed Mohammad Kazem Aghamir; Ramin Heshmat (BMC, 2024)
Abstract Background Urinary tract cancers including bladder, kidney, ureter, and pelvis are a common malignancy worldwide with high mortality ratio. Aimed to investigate the prevalence of these cancers, we conducted this study. Methods In this study, all the information related to ICD10 codes, gender, age and province of residence of individuals were obtained from the data of Iran's cancer registry by the Ministry of Health, Medicine and Medical Education and demographic evidence for each sub-country from the reports of Statistics Center of Iran (SCI). Also, the data of two Iranian national survey studies CASPIAN-III, IV, and V (information related to the care and prevention of non-communicable diseases (NCD) in childhood and adolescence) and STEPs (including information on NCD in adults over 18 years old) were used. The data was analyzed using Poisson regression with mixed effects to estimate the incidence of cancers. Results Bladder and kidney neoplasm are the most common cancers of the urinary system in Iran. The prevalence of bladder cancer has increased from 5.82 to 11.50 per 100,000 individuals. The increasing trend is growing faster in men compared with women. The incidence of kidney neoplasm has increased over the years (2.03 in 2005 vs. 7.02 in 2020 per 100,000). Having a higher incidence ratio compared with bladder cancer, kidney cancer is responsible for 35.06% of all urinary cancers in 2020 compared with 23.71% in 2005. Both neoplasms of the ureter and renal pelvis were recorded rarely and with lower incidence in both sexes during this period. Conclusion Considering the increasing trend in the incidence of urinary neoplasms in Iran during these years, the advantage of focusing on the risk of urinary cancers is highlighted. Therefore, investigating the prevalence and incidence of urinary cancers to plan and manage these cancers will result in prevention and reduction of the disease burden on the Iranian society. Future studies in this field can help in the prevention and well-timed diagnosis of these cancers.